2015
DOI: 10.1038/srep09937
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin A is Associated with Peripheral Artery Disease and Chronic Kidney Disease in Geriatrics: The Tianliao Old People (TOP) Study

Abstract: Cyclophilin A (CyPA), secreted by vascular smooth muscle cells in response to oxidative stress, is important in the pathogenesis of progressive peripheral arterial occlusion disease (PAOD), which is common among chronic kidney disease. We explored the prevalence of PAOD in Taiwan’s elderly (≥ 65 years old) population and its association with CyPA and renal function. Residents of Tianliao District, a rural community in southern Taiwan, were surveyed. An ankle-brachial index (ABI) < 0.91 was defined as PAOD. Chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 43 publications
(55 reference statements)
1
19
0
Order By: Relevance
“…We have shown that extracellular CyPA stimulates pro-inflammatory signals in endothelial cells [21,29] and others have reported that CyPA increases endothelial cell proliferation, migration, invasive capacity, and tubulogenesis in vitro [30]. Importantly, plasma CyPA levels were found to be significantly increased in patients with inflammatory diseases including peripheral artery disease [31][32][33].…”
Section: Introductionmentioning
confidence: 89%
“…We have shown that extracellular CyPA stimulates pro-inflammatory signals in endothelial cells [21,29] and others have reported that CyPA increases endothelial cell proliferation, migration, invasive capacity, and tubulogenesis in vitro [30]. Importantly, plasma CyPA levels were found to be significantly increased in patients with inflammatory diseases including peripheral artery disease [31][32][33].…”
Section: Introductionmentioning
confidence: 89%
“…The previously mentioned functional changes in vascular cells within the neointimal layer are highly dependent on the activation of TGF-β superfamily signaling. 133 - 135 The effects of TGF-β on EC depend on context. TGF-β can bind distinct receptor complexes, in which the subunits forming the receptors determine signaling specificity.…”
Section: Biology Of Avf Failurementioning
confidence: 99%
“…CYPA is a member of the immunophilin family with peptidyl prolyl cis‐trans isomerase (PPIase) activity, which is in close relationship with many physiological and pathological activities including protein folding and trafficking . CYPA has been shown to be associated with various diseases such as cardiovascular disease, kidney disease, viral infection and cancer by binding with membrane receptor or intracellular partners and activating downstream signaling pathways …”
Section: Introductionmentioning
confidence: 99%